Efektivitas Penggunaan Kitab “Al ‘Arobiyyah Bayna Yadaik” dalam Meningkatkan Prestasi Belajar Santriwati MTsTQ Al Rasyid - Umi Khoiriyah (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2021)
The Effectiveness of Using the Book “Al ‘Arabiyyah Bayna Yadayk” Volume I in Improving Arabic Learning Achievement of Female Students in Class VII B at Madrasah Tsanawiyah Tahfizhul Qur'an Al Rasyid Sukoharjo. This research is motivated by the importance of Arabic language learning within the educational context of Madrasah Tsanawiyah Tahfizhul Qur'an Al Rasyid Sukoharjo. In line with curriculum demands that emphasize mastery of the four language skills — listening, speaking, reading, and writing — the use of appropriate teaching materials becomes a key factor in achieving optimal learning outcomes. In this case, the book “Al ‘Arabiyyah Bayna Yadayk” Volume I is considered a potential learning tool to improve the Arabic understanding of the female students in Class VII B. The purpose of this study is to determine the effectiveness of using the book “Al ‘Arabiyyah Bayna Yadayk” Volume I in improving the Arabic learning achievement of Class VII B female students at Madrasah Tsanawiyah Tahfizhul Qur'an Al Rasyid Sukoharjo. This research uses a case study approach with a descriptive qualitative method. The data collection techniques used in this study include interviews, observation, and documentation. The research subjects are 28 female students from Class VII B. The results of this study show that: 1)There was a significant improvement in learning outcomes before and after using the book “Al ‘Arabiyyah Bayna Yadayk” Volume I. 2)The final evaluation results showed an average score of 84, which can be categorized as very effective. 3) Interviews with teachers and students indicated that the use of “Al ‘Arabiyyah Bayna Yadayk” Volume I has had a positive impact on improving Arabic learning achievement.